2015
DOI: 10.5194/nhessd-3-6271-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantification and analysis of geomorphic processes on a recultivated iron ore mine on the Italian island Elba using long-time ground-based LIDAR and photogrammetric data by an UAV

Abstract: Abstract. This study aims on the quantification and analysis of geomorphic processes on the barely vegetated slopes of a recultivated iron ore mine on the Italian island Elba using Terrestrial Lasercanning (TLS) and digital photogrammetry by UAV photographs over a period of 5 1/2 years. Beside this the study tried to work out the potential and the limitations of both methods to detect surface changes by geomorphic process dynamic within a natural environment. Both, UAV and TLS show the pattern of the erosion a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Lidar data were acquired during a 2‐day field campaign in November 2014 using a Terrestrial Laserscanner (TLS) Riegl VZ4000 with a maximum scanning distance up to 4,000 m. To provide high‐resolution point data of the crater and minimize shadowing effects (Haas et al, ), the scanning was done from eight different scan positions around the crater rim (e.g., Figure b). Global positions of the scan sites were provided by externally measured reflectors (dGNSS system).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lidar data were acquired during a 2‐day field campaign in November 2014 using a Terrestrial Laserscanner (TLS) Riegl VZ4000 with a maximum scanning distance up to 4,000 m. To provide high‐resolution point data of the crater and minimize shadowing effects (Haas et al, ), the scanning was done from eight different scan positions around the crater rim (e.g., Figure b). Global positions of the scan sites were provided by externally measured reflectors (dGNSS system).…”
Section: Methodsmentioning
confidence: 99%
“…Global positions of the scan sites were provided by externally measured reflectors (dGNSS system). After several postprocessing steps (Haas et al, ), including registration/referencing of every single scan position (iterative closest point [ICP]‐based algorithm; precision of the referencing: 0.007 to 0.013 m), thinning, and filtering (e.g., flying points in the Riscan Pro software, riegl.com), total number of points sums up to 60.10 6 (mean point density: 55 points per square meter). Point clouds of all single scan positions were merged and exported as ASCII files.…”
Section: Methodsmentioning
confidence: 99%
“…Unmanned Aerial Vehicles (UAVs) have integrated autopilot technology, which allows for semi-or fully autonomous navigation, flight control and image acquisition capabilities [30]. Researchers are beginning to explore the use of UAVs for the acquisition of remote sensing imagery and application in Earth surface analysis with a higher level of detail [31,32]. Several authors have already employed high resolution DSMs of cm-accuracy obtained from UAV-based imagery to monitor and quantify gully erosion [27,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Although TLS is highly accurate, and is generally treated as ''true'' results, some research has shown that it was practicable to use UAVs in MA when taking into consideration factors such as cost, accuracy, and mine size. At present, UAVs equipped with digital cameras have been used widely in MA for terrain surveying (Chen et al 2015;Esposito et al 2017;Kršák et al 2016;Lee and Choi 2015;Ozdemir and Kumral 2019), earthwork volume measurement (Hugenholtz et al 2015), three-dimensional reconstruction (Chen et al 2015;Salvini et al 2018;Xiang et al 2018), slope and geological hazard monitoring (Haas et al 2016;Malpeli and Chirico 2015;Tong et al 2015).…”
Section: Terrain Surveying and 3d Modelingmentioning
confidence: 99%
“…Examining the mechanisms of unstable slopes and monitoring them remotely are important for ensuring smooth mining operations. Studies have shown that UAVs can provide rapid identification and stability monitoring of slopes (Haas et al 2016;Francioni et al 2015;Salvini et al 2018) and mine terraces (Xiang et al 2018) in open-cast mines.…”
Section: Slope Stability Monitoringmentioning
confidence: 99%